Effect of antibiotic therapy in the postoperative period of third molar surgeries: a split-mouth, randomized and controlled study (Research, Society and Development, 2022)
Purpose: The objective of this randomized clinical trial was to evaluate the postoperative period of 32 third molars, semi-included or included, in a split mouth, of patients from the São Paulo State University. Material and Methods: The teeth were divided into two groups, in the test group drug treatment with Amoxicillin 500 mg, Dexamethasone 4 mg and Dipyrone 500 mg and in the control group patients received treatment with Dexamethasone 4 mg and Dipyrone 500 mg. The parameters used were edema, trismus and pain, measured before and after the operation, where the benefits of antibiotic therapy were evaluated. To compare the data, an analog pain scale was used, the method of Ustün, and the millimeter ruler, being submitted to Student's T test. Results: Both test and control groups had similar values, with no statistically significant difference in the incidence of postoperative complications, as well as in the presence of edema, pain and more pronounced trismus between the groups analyzed in the study. Conclusions: In view of the statistical results obtained, it was not possible to state that the use of antibiotic therapy was beneficial when related to edema, trismus and pain.